Community in Native America: Continuity and Change among the Sioux - Raymond J. DeMallie (Journal de la Société des Américanistes)
Community in Native America: Continuity and Change among the Sioux. The idea of « community », because it embodies the moral sense of a group integrated by common interest, is an important concept for understanding the social realities of American Indian life. In historical times, variations in community size and composition throughout the year brought about realignments of people according to seasonal activities. Since the creation of reservations, most American Indian communities have become sedentary, year-round settlements. This paper examines the Sioux Indians of the Great Plains ethnohistorically to track changes over time in the composition and meaning of community. In recent times, new definitions of community based on ideologies of blood and race are competing with older definitions based on kinship and face-to-face social interaction, common language, and common culture.